Designing CONNECT- a stakeholder segmentation and narrative framework for early engagement in digital tool rollouts- a case study of CCEP’s Fairmarkit (KIT) pilot - Jayasimha, Supriya (Cranfield University, 2025)
Digital transformation initiatives frequently falter after launch-not due to technology failure but because stakeholders disengage once early momentum fades. This study investigates how segmentation and narrative framing can strengthen early-stage adoption in digital tool rollouts. Focusing on the rollout of an AI-enabled procurement tool within a multinational organisation, it examines how messaging, trust, and inflow enablement shape early user acceptance. Findings indicate that long-term adoption depends less on system capability and more on how communication, ownership, and enablement are structured across stakeholder groups. Synthesising these insights with established theories of change, technology adoption, and trust, the research develops the CONNECT framework-a seven-step model (Categorise, Outline, Nominate, Nurture, Empower, Communicate, Track) translating behavioural and communicative principles into actionable design for early digital adoption. The framework bridges theoretical and practical gaps by showing how managers can create assurance-first, segmented, and feedback-driven engagement architectures that sustain participation beyond launch.
Keywords: digital transformation; stakeholder engagement; narrative framing; communication architecture; psychological safety; technology adoption; CONNECT framework; change management